Diagnostic accuracy and safety of CT-guided Lung and Mediastinal biopsies: a single center study - Asma Maqsood, Ahmed Zia Ud Din, Abdullah Saeed, Sadia Abdullah, Muhammad Junaid Tahir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Computed tomography (CT)-guided percutaneous needle biopsy plays a critical role in establishing tissue diagnosis of malignancy, guiding staging, and planning treatment for pulmonary abnormalities. Aim: To determine diagnostic accuracy and incidence of complications occurring after taking percutaneous CT-guided lung biopsy. Methodology: In this retrospective study, we evaluated 44 CT-guided chest biopsies (31 lung biopsies and 13 mediastinal biopsies) performed at our institution between September 2019 and March 2022. A coaxial core biopsy needle technique was used for all CT-guided biopsies. All procedures were performed by an experienced consultant interventional radiologist using using a commercially available helical multidetector-row CT scanner. Results: There were 29 men and 15 women among the 44 patients, ranging in age from 25 to 65 years. We found technical accuracy (described as tip of core biopsy needle within centre of lesion) of 100% (44/44) and diagnostic accuracy (described as adequate sample for histological assessment) of 97.7% (43/44) in our study. The overall incidence of complications during the procedure were recorded including pneumothorax (n = 2, 4.5%),pulmonary hemorrhage (n = 1, 2.3%), hemoptysis (n = 1, 2.3%). Conclusion: CT-guided chest biopsy is a safe procedure and has good diagnostic accuracy. However, radiologists approaching such interventional procedures must be experienced and well trained so that there are less chances of developing complications after the procedure. Practical implications: We suggest physicians performing chest biopsies to adopt better techniques and use shortest path to the lesion during needle insertion. Although CT-guided chest biopsy has fewer chances of complications, however, interventional radiologists should be conscious of potential complications. Keywords: CT-guided biopsy; Percutaneous biopsy; Imaging, Interventional radiology; Diagnosis.